Sleep quality deterioration in middle-aged and older adults living in a rural Ecuadorian village severely struck by the SARS-CoV-2 pandemic. A population-based longitudinal prospective study. Issue 8 (20th February 2021) - Del Brutto, Oscar H; Mera, Robertino M; Costa, Aldo F; Recalde, Bettsy Y; Castillo, Pablo R
Abstract: Study Objectives: This study assessed changes in sleep quality before and after the peak of the SARS-CoV-2 pandemic in community dwellers enrolled in the Atahualpa Project. Methods: Atahualpa residents aged ≥40 years were eligible if they had a Pittsburgh Sleep Quality Index (PSQI) 9 months before the pandemic and a lateral flow-based test for identification of SARS-CoV-2 antibodies during the peak of the pandemic. Six months later, individuals completed a follow-up PSQI. The independent relationship between SARS-CoV-2 infection and deterioration in sleep quality was assessed by fitting logistic mixed models for longitudinal data. Results: Of 639 participants (mean age at baseline: 59 ± 12.8 years), 325 (51%) had SARS-CoV-2 antibodies. A total of 185 (29%) individuals at baseline and 311 (49%) at follow-up were poor sleepers ( p < 0.001). Mixed logistic regression models demonstrated a significant increase in poor sleepers at follow-up (odds ratio [OR]: 2.85; 95% CI: 2.16 to 3.75), which was more marked among SARS-CoV-2 seropositive subjects (OR: 3.8; 95% CI: 2.48 to 5.81). The adjusted proportion of poor sleepers increased from 29% to 56.2% (95% CI: 50.9% to 61.6%) among SARS-CoV-2 seropositive individuals, but only to 40.7% (95% CI: 35.3% to 46.1%) in their seronegative counterparts ( p < 0.001). Likewise, progression from a good to a poor sleeper status was higher among seropositive individuals than in their seronegative counterparts (38.1% vs 22.3%; p < 0.001), after adjusting for relevant covariates. Conclusions: This study shows a deleterious effect of SARS-CoV-2 in sleep quality. An effect of SARS-CoV-2 in disrupting sleep-related pathways cannot be ruled out. Trial registration: The Atahualpa Project has been registered at ClinicalTrials.gov; the identifier number is NCT01627600, and the date was: 10/02/2012 (https://clinicaltrials.gov/ct2/show/NCT01627600?cond=Atahualpa&draw=2&rank=1 ). The Sleep Disorders substudy has been registered at ClinicalTrials.gov; the identifier number is NCT01877616, and the date was: 06/13/2013 (https://clinicaltrials.gov/ct2/show/NCT01877616?cond=Atahualpa&draw=2&rank=4 ).